Towards Effective Management of Inconsistencies in Model-Based Engineering of Automated Production Systems. Issue 3 (2015) - Feldmann, Stefan; Herzig, Sebastian J.I.; Kernschmidt, Konstantin; Wolfenstetter, Thomas; Kammerl, Daniel; Qamar, Ahsan; Lindemann, Udo; Krcmar, Helmut; Paredis, Christiaan J.J.; Vogel-Heuser, Birgit
Abstract: The development of automated production systems requires the collaborative effort of a variety of stakeholders from different disciplines. In model-based systems engineering, stakeholders address their specific concerns by forming a number of views using models. Because of the multidisciplinary nature of automated production systems, a variety of modelling languages, formalisms and tools is typically employed. Nevertheless, the aggregation of models is nowadays limited by the communication between stakeholders and interdisciplinary understanding. Therefore, in order to achieve a positive outcome of the design process it is crucial that the models are free of inconsistencies. As a first step, this paper describes challenges related to managing inconsistencies in models of systems from the domain of automated production systems. A conceptual approach that uses semantic web technologies and a technology demonstrator illustrating the technical viability of the approach are shown. Finally, requirements for a discipline-spanning inconsistency management framework are derived based on the presented challenges and initial findings from applying the approach to a demonstration case.